Penerapan Pasal 310 Ayat (3) Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan terhadap Pelaku Kecelakaan Lalu Lintas - Maimuna Latupono; Edi Setiadi (UNISBA Press, 2023)
Abstract. The background of this research is one of the Decisions of the Kayuagung District Court Number 556/Pid.Sus/2019/PN Kag concerning traffic crimes. One of the problems that arise in judicial practice is the application of articles by the Public Prosecutor and Judges in a past accident crime which is sometimes not in accordance with the actions of the defendant. This study aims to examine and find out the legal considerations of the panel of judges in imposing a sentence on the Decision of the Kayuagung District Court Number 556/Pid.Sus/2019/PN Kag. as well as the application of Article 310 paragraph (3) of Law Number 22 of 2009 concerning Traffic and Road Transportation in the Decision of the Kayuagung District Court Number 556/Pid.Sus/2019/PN Kag. This study uses a normative juridical method with the nature of analytical descriptive research, which uses secondary data. The data is obtained by analyzing the study of decisions related to research. Then the data is processed using qualitative analysis. Based on the results of the research, it is known that there was no thoroughness by the Public Prosecutor in formulating the indictment because Article 311 of Law Number 22 of 2009 concerning Road Traffic and Transportation was not used as an indictment in the decision. The judge's consideration has no correlation with the defendant's actions, so the judge's consideration does not show and does not prove that the defendant's actions have fulfilled the element of negligence in Article 310 paragraph (3) of Law Number 22 of 2009 concerning Road Traffic and Transportation. After consideration, Article 310 paragraph (3) of Law Number 22 of 2009 concerning Road Traffic and Transportation is not appropriate if it is applied in decision Number 556/Pid.Sus/2019/PN Kag because the defendant has made assumptions and caution in the verdict. Abstrak. Penelitian ini dilatar belakangi oleh salah satu Putusan Pengadilan Negeri Kayuagung Nomor 556/Pid.Sus/2019/PN Kag tentang tindak pidana lalu lintas. Permasalahan yang muncul dalam praktik peradilan salah satunya yaitu penerapan pasal oleh Jaksa Penuntut Umum maupun Hakim dalam suatu tindak pidana kecelakaan lalu yang terkadang tidak sesuai dengan perbuatan terdakwa. Penelitian ini bertujuan mengkaji dan mengetahui pertimbangan hukum oleh majelis hakim dalam menjatuhkan pidana pada Putusan Pengadilan Negeri Kayuagung Nomor 556/Pid.Sus/2019/PN Kag. serta penerapan Pasal 310 ayat (3) Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan dalam Putusan Pengadilan Negeri Kayuagung Nomor 556/Pid.Sus/2019/PN Kag. Penelitian ini menggunakan metode yuridis normatif dengan sifat penelitian deskriptif analitis, yang menggunakan data sekunder. Data diperoleh dengan cara menganalisis studi putusan yang berkaitan dengan penelitian. Kemudian data diolah dengan menggunakan analisis kualitatif. Berdasarkan hasil penelitian diketahui bahwa tidak adanya ketelitian Penuntut Umum dalam merumuskan surat dakwaan karena Pasal 311 Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan tidak dijadikan dakwaan dalam putusan tersebut. Pertimbangan hakim tidak memiliki korelasi dengan perbuatan terdakwa, sehingga pertimbangan hakim dinilai tidak memperlihatkan dan tidak membuktikan bahwa perbuatan terdakwa telah memenuhi unsur kelalaian Pasal 310 ayat (3) Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan. Setelah dilakukannya pertimbangan, Pasal 310 ayat (3) Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan tidak tepat jika diterapkan dalam putusan Nomor 556/Pid.Sus/2019/PN Kag karena terdakwa telah mengadakan pendugaan dan penghati-hatian dalam putusan tersebut.